Carbon Transformations of Biochar Based Co-Composting - A Review - Pandiyan, Balaganesh; Mangottiri, Vasudevan; Narayanan, Natarajan (Mini-Reviews in Organic Chemistry, 2021)
Biochar-Amended Composting (BAC) plays an integral role in sustainable agricultural practices due to its multiple benefits in crop production, soil nutrient retention, carbon sequestration and environmental protection. Although accepted as a traditional method, there is a lack of understanding in defining its suitability and efficiency in terms of various base-materials and conditions. Being two carbon-based entities with plentiful nutrients and surface activity, biochar and compost find application in agricultural fields together or separately for improving the soil properties and crop productivity. Recent studies focus on defining the optimum conditions for their preparation, mixing, application and monitoring under various feed, soil, crop and climatic conditions. However, due to the complexity and specificity of the system, many influencing aspects of their interaction are yet unknown in detail. In this review, we analyze the recent advancements in the selection and preparation of new materials for BAC, and explain the mechanisms of Organic Matter (OM) degradation/sequestration occurring in soil based on possible chemical/morphological transformations of organic carbon. Most of the performance results are in agreement with the previous records, but a few contradictions have been observed under diverse experimental conditions. In general, BAC enhanced the mineralization of carbon and sequestration of heavy metals, and stabilized labile fraction of OM due to the development of carbonyl, phenolic and aromatic functional groups on its surface. In addition, aging of biochar resulted in stable N-C=O and amino groups for the adsorption of nitrogen compounds thus decreasing the potential greenhouse gas emissions. The study further identifies potential future research gaps in this area.
Keywords: carbon sequestration